Die mikrostrukturele bewerking van affikse in Afrikaanse vertalende woordeboeke - de Wet, Gerda (Lexikos, 1999)
The Microstructural Treatment of Affixes in Afrikaans Translation Dictionaries The microstructural treatment of affix lemmata in Afrikaans translation dictionaries is currently inadequate. In the dictionaries under discussion, namely Tweetalige Woordeboek / Bilingual Dictionary (BD) and Groot Woordeboek / Major Dictionary (MD) which are presently viewed as the leading translation desk-top dictionaries, affixes are included rarely. And if they are included as affix lemmata, their treatment is cursory. BD and MD are not very user-friendly and force the user to rely largely on his/her intuition for the meaning and use of affix lemmata. Consequently these dictionaries do not consistently fulfil their role as sources of information. This article considers a number of information categories according to which the lexicographer should treat affix lemmata in the dictionary so that they may be of value to the user. These categories include semantic information such as polysemy, homonymy and synonymy, etymological information, as well as pronunciation and grammatical information.